Vernoa Hildebranditii, Acacia stuhlmannii and Moringa Oleifera Leaf and Root-bark Extracts Exhibit Antimicrobial Effects on Selected Diarrheagenic Microorganisms - Mwabonje, Ronald; Makonde, Huxley; Kanga, Ali Juma; Adem, Aggrey; Saidi, Suleiman; Jeza, Victor Tunje (Multidisciplinary Journal of Technical University of Mombasa, 2020)
Infectious diseases are the main causes of morbidity and mortality worldwide. There is increasing concern of indiscriminate use of antibiotics and incidences of multiple antibiotic resistances in human pathogens. The potential of higher plants as source of new drug leads has been demonstrated but is still under explored. In Africa and most developing countries, traditional medicine still forms the backbone of rural medicinal practice. Although a number of American and Asian countries medicinal herbs have been evaluated scientifically and their medicinal properties demonstrated. In Africa, attempts to evaluate medicinal plants in relation to their biological activities and medicinal usefulness are limited. The emergence of antibiotic resistance has led to increased use of herbal medicine as an alternative to combat various ailments. This study aimed at determining the antimicrobial activity of Vernoa hildebrandtii, Acacia stuhlmannii and Moringa oleifera leafy and root bark extracts using disc diffusion technique. Crude extracts were obtained from dried powder by single solvent maceration with ethanol and water. Bioassays were used to evaluate the bioactivity of the extracts against Escherichia coli and Staphylococcus aureas. Antimicrobial activity was determined by measuring the zones of growth inhibition in mm. Moringa aleifera root water extract was the most potent fraction with bioactivity arrange of between 6-32 mm followed by Acacia stuhlmannii root bark water extracts with bioactivity range between 12-31 mm and Moringa oleifera root bark with bioactivity range of between 6-29 mm. Vernoa hildebrandtii leave alcohol and Acacia stuhlmannii Taub root bark- alcohol extract had bioactivity range of between 9-28 and 5-28, respectively. However, Acacia stuhlmannii leaf extracts did not show any antimicrobial activities. The antimicrobial effects of the plant extracts were dose dependent. These findings validate what have been known about Moringa oleifera. They also demonstrate potential biochemical agents in Vernoa hildebrandtii and Acacia stuhlmannii extracts in the management of diarrheagenic microorganisms